2015
DOI: 10.3957/056.045.0342
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Spatial and Temporal Variation in the Diet of Cape Clawless Otters (Aonyx capensis) in Marine Environments

Abstract: We studied the diet of Cape clawless otters (Aonyx capensis) at three sites along the eastern and southern coast of South Africa to assess possible spatial variation along a community species richness and biomass gradient associated with rocky shores. A total of 309 spraints representing two seasons (summer 2013/2014 and winter 2014) were collected and subsequently analysed. The percentage occurrence and percentage dry mass of numerous prey categories were compared between sites and seasons. Variation in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 34 publications
2
11
1
Order By: Relevance
“…Grant and Harrington () assumed that the reduced consumption of fish during summer may be related to the effects of water temperature on fish metabolism: fish swim faster in summer, thus being more difficult to catch, whereas their slower metabolism in winter reduces their swimming speed, which makes them more vulnerable to predation. This pattern has been observed even in marine environments in a study on African Cape clawless otters, Aonyx capensis (Schinz, 1821) (Jordaan, McIntyre, Somers, & Bester, ).…”
Section: Discussionmentioning
confidence: 66%
“…Grant and Harrington () assumed that the reduced consumption of fish during summer may be related to the effects of water temperature on fish metabolism: fish swim faster in summer, thus being more difficult to catch, whereas their slower metabolism in winter reduces their swimming speed, which makes them more vulnerable to predation. This pattern has been observed even in marine environments in a study on African Cape clawless otters, Aonyx capensis (Schinz, 1821) (Jordaan, McIntyre, Somers, & Bester, ).…”
Section: Discussionmentioning
confidence: 66%
“…The present study sheds new insight on our knowledge of the diet composition of the African clawless otters. Previously, crabs and other crustaceans were regarded as the preferred and primary prey while fish, mollusks, and frogs were secondarily important (Rowe-Rowe, 1977;van der Zee, 1981;Arden-Clarke, 1986;Kruuk and Goudswaard, 1990;Nowak, 1991;Butler and du Toit, 1994;Ligthart et al, 1994;Kingdon, 1997;Somers, 2000;Lariviere, 2001;Somers and Nel, 2003;Emmerson and Philip, 2004;Ogada, 2006;Jordaan et al, 2015). Our study showed that fish was the dominant prey item in and around Lake Tana during both wet and dry seasons.…”
Section: Discussionmentioning
confidence: 80%
“…The diet of African clawless otter has been studied by Kruuk and Goundswaard (1990) in Lake Victoria, Butler and du Toit (1994) in Zimbabwe, Rowe-Rowe (1977), van der Zee (1981), Verwoerd (1987), Perrin and Carugati (2000), Somers (2000), Somers and Nel (2003), Watson and Lang (2003), Jordaan et al (2015) in South Africa and Ogada (2006) in Kenya. However, scientific data on the ecology of the species in Lake Tana is not available and elsewhere in Ethiopia is not available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to studies based primarily on scat (spraint) analysis, African clawless otters (Aonyx capensis) feed predominantly on fish, frogs and crabs and occasionally other taxa such as insects (Rowe-Rowe and Somers, 1998;Somers and Nel, 2003). In marine locations, crabs dominate the diet of this species with fish present in lower proportions (van der Zee, 1981;Somers, 2000;Emmerson & Phillip, 2004;Jordaan et al, 2015). This pattern is also observed in freshwater locations (Rowe-Rowe, 1977b;Kruuk and Goudswaard, 1990;Somers and Purves, 1996;Somers and Nel, 2003) which suggests a preference for benthic and/or slow-moving prey.…”
Section: Introductionmentioning
confidence: 79%